MANAGEMENT DECISION SUPPORTBY USING EARLY WARNING ENVIRONMENTS - Žilinskas, Raimundas; Skyrius, Rimvydas (Ekonomika, 2009)
Successful activities in a dynamic environment of today’s economy largely depend on the skills to have an adequate view of activity environment and its changes. The information activities of business decision makers relate their subjective potential of environment assessment and problem solving to the systems of environment monitoring and early warning, whose relevance is of expressed in various activities both at micro and macro levels. The paper discusses the features of the bank deposit insurance system in the Republic of Lithuania, its information needs and the role of early warning systems in its activities. Also, the paper examines a prototype of an early warning system in the Deposit Insurance Scheme of the Republic of Lithuania and the conditions for its application. There are specific groups of decision-important information and relations between their estimates. The proposed way of applying a composite set of decision criteria can be transferred to similar systems in other fields of activity. p>